Merancang Masa Depan Bisnis: Implementasi Arsitektur Enterprise dengan Metodologi Zachman - Budi Sukmawan (CV. ULIL ALBAB CORP, 2024)
Strategy and policy in a profit-oriented organization such as a consulting firm require the support of the right information system to win the competition in an increasingly competitive business world. Companies are required to be able to develop information systems to help business activities, achieve organizational goals and services for stakeholders. Enterprise Architecture Planning (EAP) from the Zachman framework as one of the methods or reference frameworks for building an information architecture that is oriented to business needs which consists of data architecture, applications and technology as well as an implementation plan for the architecture that has been created to support business activities in order to achieve the organization's mission. EAP explains the data architecture, applications and technology needed to support the organization's business.